2017
DOI: 10.3390/math5040057
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Connections: Connecting Points

Abstract: This study introduces a procedure to obtain all interpolating functions, y = f (x), subject to linear constraints on the function and its derivatives defined at specified values. The paper first shows how to express these interpolating functions passing through a single point in three distinct ways: linear, additive, and rational. Then, using the additive formalism, interpolating functions with linear constraints on one, two, and n points are introduced as well as those satisfying relative constraints. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(130 citation statements)
references
References 6 publications
(12 reference statements)
0
115
0
Order By: Relevance
“…(7) Extension to nonlinear DEs. (8) Extension to partial DEs. (9) Extension to nonlinear constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) Extension to nonlinear DEs. (8) Extension to partial DEs. (9) Extension to nonlinear constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The linear constraints considered in the theory of connections [8] are any linear combination of the function and/or its derivatives evaluated at specified values of the independent variable, t. For an assigned set of n independent functions, h k (t), the n constraints of the DE allow us to derive the unknown vector of coefficients, η. By substituting this expression into Equation (3), we obtain an equation satisfying all the constraints, no matter what g(t) is.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that this still solved the differential equation with an accuracy on the order of O(10 −7 ). This can be explained by an equation first presented in the seminal paper on TFC [29]. In this paper an equation (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The Theory of Functional Connections (TFC) is a new technique that analytically derives a constrained expression which satisfies the problem's constraints exactly while maintaining a function that can be freely chosen [7]. This theory, initially called "Theory of Connections", has been renamed for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…This approach discretizes the domain about collocation points, and the solution of the DE is expressed by a sum of "basis" functions with unknown coefficients that are approximated in order to satisfy the DE as closely as possible. Yet, in order to incorporate boundary conditions, one or more equations must be added to enforce the constraints.The Theory of Functional Connections (TFC) is a new technique that analytically derives a constrained expression which satisfies the problem's constraints exactly while maintaining a function that can be freely chosen [7]. This theory, initially called "Theory of Connections", has been renamed for two reasons.…”
mentioning
confidence: 99%